2009
DOI: 10.2148/benv.35.4.563
|View full text |Cite
|
Sign up to set email alerts
|

Floods and Residential Property Values: A Hedonic Price Analysis for the Netherlands

Abstract: The central question addressed in this article is whether floods have an impact on residential property values. In the Netherlands floods of the Meuse river in 1993 and 1995 had negative effects on prices of the houses that were affected; specifically a decrease of about 9 per cent. An analysis of sales in municipalities along the river during the decade after this period reveals that this price decrease has been permanent. We also find countervailing effects related to water: a location close to the water has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…On the contrary, as we move 10% further away from the nearest large river, house prices increase with 0.004%. Although this is a relatively small price increase, this positive relationship may hint at the possible impact of flood risks on house prices [ Daniel et al ., ]. Switzerland is subject to riverine flooding on an annual basis [ Hausmann et al ., ], and the greatest flood catastrophe of the last 40 years took place in 2005.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, as we move 10% further away from the nearest large river, house prices increase with 0.004%. Although this is a relatively small price increase, this positive relationship may hint at the possible impact of flood risks on house prices [ Daniel et al ., ]. Switzerland is subject to riverine flooding on an annual basis [ Hausmann et al ., ], and the greatest flood catastrophe of the last 40 years took place in 2005.…”
Section: Resultsmentioning
confidence: 99%
“…In this issue Daniel et al (2009) conclude that their 9 per cent discount for houses affected by the floods of the River Meuse in the Netherlands is relatively high in international comparison. Surprisingly, studies of flooding in the European context are rare.…”
Section: Negative Impactsmentioning
confidence: 90%
“…Examples of studies investigating the latter hypothesis can be found in the voluminous hedonic-pricing literature (Bin and Polasky 2004;Bin et al 2008;Bin and Landry 2013;Atreya et al 2013;Daniel et al 2009b). These studies typically investigate whether disasters such as floods lead to house price disparities between risky and non-risky locations.…”
Section: Household Migration and Risk Judgmentsmentioning
confidence: 99%